Artistic expertise shapes face perception: An alpha frequency and N170 study on portraiture - Joana Pereira Seabra; Laura Kaltwasser; Maik Mylius; Vittorio Gallese (NeuroImage: Reports)
Expertise in several areas appears to modulate neurocognitive processes. These processes have been observed to differ in visual arts experts compared to the general population. Here, we aimed to investigate whether visual artists' neural responses to tasks within and outside their field of expertise are contrasting to the responses of non-experts. Fifteen visual artists' and fifteen non-artists’ EEG measures were recorded as each participant was presented with two consecutive tasks: face perception and drawing. Face perception activities were assessed by comparing the groups’ amplitude and latency of the N170 in response to complete and incomplete faces. Artists exhibited a larger N170 amplitude to facial stimuli than non-artists, pointing toward significance. Complete faces elicited the stronger response for both groups. A cluster-based permutation test showed that alpha frequency, previously linked to expertise, significantly differed between the artist and nonartists groups during drawing. Our results suggest differing neurocognitive processing for artists compared to non-artists in both field-specific and nonfield-specific tasks, in that expertise in drawing impacts neuronal activity in response to faces.